Sports Performance 2015
DOI: 10.1007/978-4-431-55315-1_20
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Considerations in Cross-Country Skiing

Abstract: Crosscountry skiing is a four-legged gait, and some gait patterns, such as 2-skate skiing, are similar to those adopted by animals (galloping horse). Four-legged animals change gait patterns with increasing speeds of locomotion, at least in part, to minimize metabolic energy expenditure. For example, a horse will switch from a walk, to a trot, and finally to a gallop as speed of locomotion increases. Similarly, skate crosscountry skiers will switch from a 2-skate gait to a 1-skate gait with increasing speeds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…One main similarity between these two sub-techniques is that of one double poling movement on every second ski push. Based on that, Herzog et al (2015) considered G2 and G4 to be the same unique sub-technique. However, in the present study, we find large differences in both forward, lateral and vertical movement of the CoM throughout the skiing cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One main similarity between these two sub-techniques is that of one double poling movement on every second ski push. Based on that, Herzog et al (2015) considered G2 and G4 to be the same unique sub-technique. However, in the present study, we find large differences in both forward, lateral and vertical movement of the CoM throughout the skiing cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Herzog et al (2015) showed that these transitions between sub-techniques indeed occur. However, since both G2 and G4 have only one pole push for every second leg/ski push, they characterised both G2 and G4 as the same sub-technique, labelled 2-skate.…”
Section: Introductionmentioning
confidence: 98%